(untitled) (International Seven Journal of Multidisciplinary, 2023)
The global sports and media industries are undergoing a transformative shift driven by the convergence of commercial innovation and data intelligence. Traditional broadcast models, which once limited sports consumption to scheduled programming, are now evolving into on-demand, personalized, and immersive experiences. This article explores how advancements in immersive technologies, such as extended reality (XR) – including virtual reality (VR), augmented reality (AR), and mixed reality (MR) – and artificial intelligence (AI) are reshaping sports media and fan engagement. These technologies allow fans to step beyond passive viewership, becoming active participants in their experience, a concept referred to as "actience" which emerged from SXSW 2025 discussions. This shift toward immersive fan experiences is not just altering how sports content is consumed but also how it is created, distributed, and monetized. The article further explores how data intelligence is optimizing fan experiences both in-stadium and online through smart venues and personalized content. Real-time analytics are enabling sports franchises to enhance fan engagement, optimize operational efficiency, and generate new revenue streams. Additionally, the paper addresses the growing emphasis on accessibility and inclusivity within immersive sports content, ensuring that new technologies cater to a diverse audience. Through a comprehensive review of recent academic literature, including key studies presented at SXSW 2025, the paper discusses the future of sports media in an increasingly digital and data-driven world. The integration of XR and AI is not only revolutionizing fan loyalty and retention but also creating new opportunities for sports organizations to build sustainable, interactive, and personalized experiences for global audiences. Ultimately, this article highlights the pivotal role of immersive technologies and data intelligence in shaping the future of sports and media, with profound implications for the business models and fan engagement strategies of the industry.